Marriage Appreciation Trust Viewed From Indonesian Positive Law - Rafiqa Sari; Tiara Ramadhani; Darwance Darwance (Universitas Muhammadiyah Purwokerto, 2023)
Indonesian society is the society it consists of from various ethnicity, nation, culture, religion and beliefs are diverse . Indonesian citizen, deep matter implementation his marriage subject to Law No. 1 of 1974, however only for people whose religion and beliefs recognized by the state. Objective from study This is analyze validity marriage devout trust seen from regulation the prevailing laws and regulations in Indonesia. Study This done with use method law normative through studies library. The resulting research results is after legalized Regulation Government Number 40 of 2019 concerning Implementation Constitution Number 24 of 2013 concerning Administration Population. So that he admitted marriage devout trust in Indonesia in law positive, with implementation marriage through procedures that have determined in regulation legislation. Is one _ proof that law positive in Indonesia, admitted existence devout trust after exists decision court Constitution.Keywords: Marriage, Appreciation Trust, Positive Law